2021
DOI: 10.21037/gs-20-670
|View full text |Cite
|
Sign up to set email alerts
|

Is primary total pancreatectomy in patients with high-risk pancreatic remnant justified and preferable to pancreaticoduodenectomy? —a matched-pairs analysis of 200 patients

Abstract: Background: Total pancreatectomy (TP) eliminates the risk of postoperative pancreatic fistula (POPF) and its associated secondary complications. Hence, it may theoretically offer advantages over pancreaticoduodenectomy (PD) regarding early postoperative outcome of patients with high-risk pancreatic remnant.Methods: Ninety-day mortality and morbidity of 100 TP vs. 100 PD for pancreatic head lesions were retrospectively compared. Groups were matched for pancreatic texture, pancreatic duct size, final histology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 38 publications
(57 reference statements)
0
36
3
Order By: Relevance
“…16 The national database from the American College of Surgeons revealed higher major morbidity and a doubled 30-day mortality rate (6% vs. 3%) after TP in comparison to PD. 39 In contrast, others demonstrated comparability 8,[13][14][15]18,40,41 in major morbidity (19-30% vs. 26-37%) 8,14,18,19 and perioperative mortality (0-7% vs. 0-5%) 8,[13][14][15]18,19,41 from which four studies matched both groups. [13][14][15]18 One single-center study compared TP versus PD with high-risk PJ (Fistula Risk Score 7-10), revealing no differences in major morbidity, 17 whereas Luu et al compared TP indicated for high-risk pancreatic remnant versus high-risk PD, demonstrating comparable major morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The national database from the American College of Surgeons revealed higher major morbidity and a doubled 30-day mortality rate (6% vs. 3%) after TP in comparison to PD. 39 In contrast, others demonstrated comparability 8,[13][14][15]18,40,41 in major morbidity (19-30% vs. 26-37%) 8,14,18,19 and perioperative mortality (0-7% vs. 0-5%) 8,[13][14][15]18,19,41 from which four studies matched both groups. [13][14][15]18 One single-center study compared TP versus PD with high-risk PJ (Fistula Risk Score 7-10), revealing no differences in major morbidity, 17 whereas Luu et al compared TP indicated for high-risk pancreatic remnant versus high-risk PD, demonstrating comparable major morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]18 One single-center study compared TP versus PD with high-risk PJ (Fistula Risk Score 7-10), revealing no differences in major morbidity, 17 whereas Luu et al compared TP indicated for high-risk pancreatic remnant versus high-risk PD, demonstrating comparable major morbidity and mortality. 18 Marchegiani et al compared intraoperatively converted PD to TP for any indication versus high-risk PD (alternative Fistula Risk Score), demonstrating a trend to significantly lower major morbidity (19% vs. 31%) after TP as consequence of lower rates of peripancreatic collections, intra-abdominal abscesses, sepsis, and haemorrhages among others. However, 90-day mortality rates were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strategies include disconnection followed by exteriorization and bridge stenting may be used in some scenarios. Revising pancreaticoenteric anastomosis and switching to other techniques is not feasible in most of these scenarios and should not be done (141)(142)(143)(144)(145)(146)(147)(148)(149)(150).…”
Section: Post-operative Mitigation Strategies: Proactive Preemptive A...mentioning
confidence: 99%
“…Recently, three studies compared this particular group of high-risk PD procedures with TP in terms of surgical outcome, and reported mainly better results after TP. [3][4][5] Regarding quality of life, a retrospective analysis by Marchegiani et al 5 described comparable results after TP and high-risk PD. To prevent pancreoprivic diabetes or to preserve at least partial endogenous insulin secretion to mitigate the psychosocial aspects of diabetes or lifelong insulin therapy, intraportal islet autotransplantation should be also considered.…”
mentioning
confidence: 98%